2022
DOI: 10.1111/sms.14244
|View full text |Cite
|
Sign up to set email alerts
|

Neural and contractile determinants of burst‐like explosive isometric contractions of the knee extensors

Abstract: Walking and running are based on rapid burst‐like muscle contractions. Burst‐like contractions generate a Gaussian‐shaped force profile, in which neuromuscular determinants have never been assessed. We investigated the neural and contractile determinants of the rate of force development (RFD) in burst‐like isometric knee extensions. Together with maximal voluntary force (MVF), voluntary and electrically evoked (8 stimuli at 300 Hz, octets) forces were measured in the first 50, 100, and 150 ms of burst‐like qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…It is unsurprising that repetitive explosive contractions impair the neural drive as neural drive is the main determinant of rapid contractions. 20,21,44 Indirect evidence of decreased muscle excitation and motor unit recruitment occurrence could also be found in the significant drop of normalized RMS (d ~ 1.0) and normalized MFCV (d ~ 0.6) over the first 50-100 ms of contractions. To remove the effect of sarcolemma property changes, we normalized each RMS estimate to the corresponding M-wave peak-topeak amplitude and the MFCV estimate by the M-wave CV.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is unsurprising that repetitive explosive contractions impair the neural drive as neural drive is the main determinant of rapid contractions. 20,21,44 Indirect evidence of decreased muscle excitation and motor unit recruitment occurrence could also be found in the significant drop of normalized RMS (d ~ 1.0) and normalized MFCV (d ~ 0.6) over the first 50-100 ms of contractions. To remove the effect of sarcolemma property changes, we normalized each RMS estimate to the corresponding M-wave peak-topeak amplitude and the MFCV estimate by the M-wave CV.…”
Section: Discussionmentioning
confidence: 97%
“…In turn, spinal and supraspinal mechanisms have likely lowered the motor unit recruitment and discharge rate in the first phase of voluntary contractions. It is unsurprising that repetitive explosive contractions impair the neural drive as neural drive is the main determinant of rapid contractions 20,21,44 . Indirect evidence of decreased muscle excitation and motor unit recruitment occurrence could also be found in the significant drop of normalized RMS ( d ~ 1.0) and normalized MFCV ( d ~ 0.6) over the first 50–100 ms of contractions.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether and in contrast to that observed for maximal muscle strength (peak torque), the present RTD data clearly indicate that a separate familiarization session is necessary to improve the motor coordination required for reaching true maximal explosive muscle force production and to achieve acceptable reliability for KE RTD in adults with obesity. Both early and late phase RTD, which mainly represents neural and muscular determinants, respectively (Cossich & Maffiuletti, 2020; D'Emanuele et al, 2023; Tillin et al, 2010), benefit from familiarization. It has previously been demonstrated that co‐contraction of the antagonist occurs in people who are not habituated to a specific task that requires rapid force production (Duchateau & Enoka, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, only a single previous study has assessed the test−retest reliability of isometric KF RTD, which was examined in healthy young males and females using isokinetic dynamometry (Mentiplay et al, 2015). (Cossich & Maffiuletti, 2020;D'Emanuele et al, 2023;Tillin et al, 2010), benefit from familiarization. It has previously been demonstrated that co-contraction of the antagonist occurs in people who are not habituated to a specific task that requires rapid force production (Duchateau & Enoka, 2002).…”
Section: Rapid Force Capacity (Rtd)mentioning
confidence: 99%
“…This physiological feature of RFD may explain why this variable is often more sensitive to changes than MVF [ 16 ], especially when the fatiguing task comprises rapid force production [ 17 ]. The analysis of muscle excitation in the first 50 ms of contraction employing high-density electromyography (HD-EMG) might provide even more insights into the causes of possible decrement of early RFD [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%